West Antarctic Rift system: a possible New Zealand-Patagonia Oligocene paleobiogeographic link - Casadio, Silvio Alberto (2010)
Crucial oceanographic modifications took place in the Southern Hemisphere during the period between 35 and 15 Ma. These included the establishment of broad zonal belts of surface-water masses separated by oceanic fronts. These belts had a paramount role in the isolation and evolution of the marine faunas in the Southern Hemisphere. However, paleontological evidence demonstrates that during this period paleobiogeographic connections between New Zealand and Patagonia were maintained, as shown by the presence of numerous common taxa. Here we postulate that the paleobiogeographic connection may have been along the West Antarctic Rift System (WARS). This system underwent an episode of significant extension during the Eocene-Oligocene and at the same time the full opening (c. 31 Ma) of the Tasmanian gateway possibly elicited the onset of a proto-circum-Antarctic flow of cold waters, perhaps through a West Antarctic seaway connecting the southern Pacific and Atlantic Oceans. While conclusive support for this hypothesis is presently limited, information assembled during the last decade after research in McMurdo Sound is very enlightening and there is an accumulating body of tectonic, sedimentary and paleontological information that the WARS could have afforded a principal paleobiogeographic seaway linkage between New Zealand and Patagonia in the Oligocene.